Hubungan Personal Branding Influencer sebagai Ambassador Vaksin dengan Kepercayaan Followers pada Vaksin - Faikar Hafizh; O. Hasbiansyah (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Risa Saraswati is an influencer on Instagram who is also a writer and content creator on the Jurnnalrisa Youtube channel. Risa Saraswati was chosen by the Bandung City government to be one of the people who administered the Covid 19 vaccine and is expected to be able to influence the public. The purpose of this study was to determine the relationship between Risa Saraswati's Personal Branding with Followers’ Trust on the @halobandung’s Instagram account. This study uses the S-R theory which bases the assumption that behavior change occurs depending on the quality of the stimulus (stimulus) that communicates with the organism. Then, the method used in this research is quantitative with a correlational approach. Sampling using simple random sampling technique. The population in this study are followers of the Instagram account @halobandung, with the sampling technique using the slovin formula and the results obtained are 100 respondents. Data obtained through questionnaires were distributed to respondents. The measurement scale in this study is the Likert scale. Test the validity and reliability test using the SPSS application, with the Cronbach test technique. The results of this study are that there is a strong and significant relationship between personal branding influencers and the trust of followers of the @halobandung Instagram account on the covid19 vaccine. There is a strong relationship between influencer competency and the trust of followers of the @halobandung Instagram account on the covid19 vaccine, there is a strong relationship between style influencers and the trust of followers of the @halobandung Instagram account on the covid19 vaccine, there is a strong relationship between standard influencers and the trust of followers of the Instagram account @halobandung on the COVID-19 vaccine. Abstrak. Risa Saraswati merupakan influencer di Instagram yang juga seorang penulis dan content creator di channel Youtube Jurnnalrisa. Risa Saraswati dipilih oleh pemerintah Kota Bandung untuk menjadi salah satu orang yang melakukan vaksin covid 19 dan diharapkan mampu mempengaruhi khalayak. Penelitian ini dilakukan untuk mengetahui Hubungan Personal Branding Risa Saraswati Dengan Kepercayaan followers Pada Vaksin Covid19 di akun Instagram @halobandung. Penelitian ini menggunakan teori S-R yang mendasarkan asumsi yang mana perubahan perilaku terjadi tergantung kepada kualitas rangsangan (stimulus) yang berkomunikasi dengan organisme. Lalu, metode yang digunakan dalam penelitian ini adalah kuantitatif dengan pendekatan korelasional. Pengambilan sampel menggunakan teknik simple random sampling. Populasi dalam penelitian ini adalah followers akun Instagram @halobandung, dengan teknik pengambilan sampel menggunakan rumus slovin dan hasil yang didapat sebesar 100 responden. Data yang didapat melalui kuesioner disebar ke responden. Skala pengukuran dalam penelitian ini adalah skala likert. Uji validitas dan uji reliabilitas menggunakan aplikasi SPSS, dengan teknik uji Cronbach. Hasil dari penelitian ini adalah terdapat hubungan yang kuat dan signifikan antara personal branding influencer dengan kepercayaan followers akun Instagram @halobandung pada vaksin covid19. Terdapat hubungan yang cukup kuat antara competency influencer dengan kepercayaan followers akun Instagram @halobandung pada vaksin covid19, adanya hubungan yang kuat antara style influencer dengan kepercayaan followers akun Instagram @halobandung pada vaksin covid19, adanya hubungan yang kuat antara standard influencer dengan kepercayaan followers akun Instagram @halobandung pada vaksin covid19.